2010
DOI: 10.1590/s1806-66902010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Balanço energético para a produção de biodiesel pela cultura da mamona (Ricinus communis L.)

Abstract: Balanço energético para a produção de biodiesel pela cultura da mamona (Ricinus communis L.) 1 Energy balance for biodiesel production by the castor bean crop (Ricinus communis L.) Palavras-chave -Eficiência energética. Consumo de energia. Produção de energia.Abstract -The castor bean crop (Ricinus communis L.) has acquired prestige due to industries interest in the oil quality and recently for new sources of energy demand. The experiment that served as basis for the data used in this study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
5
Order By: Relevance
“…However, the productivity increase in the area under irrigation during the whole cycle reached 85.89% (Table 4). Fertilizers and diesel oil were the main energy inputs (Figure 3) likewise observed by Checheto et al (2010) and Jordan et al (2012a), coming after only electricity, the main input in irrigated areas given the power consumed by the pumping system.…”
Section: Resultsmentioning
confidence: 89%
“…However, the productivity increase in the area under irrigation during the whole cycle reached 85.89% (Table 4). Fertilizers and diesel oil were the main energy inputs (Figure 3) likewise observed by Checheto et al (2010) and Jordan et al (2012a), coming after only electricity, the main input in irrigated areas given the power consumed by the pumping system.…”
Section: Resultsmentioning
confidence: 89%
“…Similar results were found by JASPER et al (2010), to characterize the power consumption for direct seeding of Crambe abyssinica. On the other hand, castor beans, under conventional cultivation, presented the highest energy expenditure during the preparation of the soil (CHECHETTO et al 2010). SALLA et al (2010a) reported that the most representative items of the technical itinerary in the production of corn under a conventional management were the inputs, with 77.5% of total cultural inputs.…”
Section: Resultsmentioning
confidence: 99%
“…Para esta mesma lâmina, a cultivar IAC 2028 apresentou relação de 2,59. Chechetto et al (2010), trabalhando com mamona, verificaram valor de 2,45, para a relação entre energia dos grãos e energia utilizada na fase agrícola (semeadura à colheita), para uma produtividade de 1.400 kg ha Gazzoni et al (2007) e Chechetto et al (2010). Em segundo lugar, vem o óleo diesel e lubrificantes, sendo superados pela energia elétrica apenas no tratamento com lâmina de irrigação de 162,0 mm, onde esta representou 27% da energia empregada.…”
Section: Resultsunclassified
“…Chechetto et al (2010) consideraram desprezível a energia referente à mão de obra, em seu estudo, já que todas as operações foram mecanizadas. Campos et al (2009) Figura 4.…”
Section: Resultsunclassified
See 1 more Smart Citation